Method for preparing ceramsite sand based on blast furnace slag and iron tailings

Preparation of ceramic sand by blast furnace slag and iron tailings solves the problems of high cost of oil fracturing proppant materials and difficult waste disposal, and provides low-density, high compressive strength and high temperature resistance, realizing resources and cost reduction.

CN119191869APending Publication Date: 2024-12-27HEBEI PETROLEUM VOCATIONAL & TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411313110.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing petroleum fracturing proppant materials such as quartz sand, ceramics and coated proppants have high density, complex manufacturing and high cost problems, which are difficult to meet the special requirements of the petroleum industry for strength, density, high temperature resistance and chemical stability. At the same time, the resource treatment technology of blast furnace slag and iron tailings is insufficient, which leads to difficulties in waste disposal.

Method used

The method of preparing ceratops and iron tailings is used to prepare ceratops and ferrous tailings. By selecting kaolin, blast furnace slag, ferrous tailings and bentonite for grinding, mixing, granulating, drying and sintering, ceramic sand with excellent properties is prepared. Use of petroleum fracturing proppant.

Benefits of technology

The resource utilization of blast furnace slag and iron tailings has been realized, the production cost of ceratops sand has been reduced, and the production cost of ceratops sand is provided with low density, high compressive strength and high temperature resistance. It is suitable for petroleum fracturing proppants and solves the material. High cost and difficult waste disposal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191869A_ABST
    Figure CN119191869A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing ceramsite sand based on blast furnace slag and iron tailings. The method specifically comprises the steps of S1, material preparation, S2, grinding, S3, mixing, S4, granulation, S5, drying, S6, sintering and S7, screening and grading (according to the particle size) after discharging from a furnace and packaging. The ceramsite sand is produced by utilizing industrial wastes, namely the blast furnace slag and the iron tailings, waste utilization of the blast furnace slag and the iron tailings is realized, and the ceramsite sand produced by adopting the method can also be used as a petroleum fracturing propping agent and has the characteristic of lower production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation of ceramsite sand, and in particular to a method for preparing ceramsite sand based on blast furnace slag and iron tailings. Background Art

[0002] The general requirements for strength and density of petroleum fracturing proppants are as follows:

[0003] 1. Compressive strength and wear resistance: ceramsite proppants should be able to withstand pressures at different depths (such as 52MPa, 69MPa, 86MPa, 102MPa) and maintain high strength. 2. Low density: The relative density of proppant particles should be low to facilitate pumping into the well. Apparent density or volume density is a commonly used expression method. For example, quartz sand may be 1.76g / cm 3 The ideal proppant density should be as low as possible to reduce pumping difficulty, equipment wear and fracturing costs. The apparent density of the proppant is less than 2.75g / cm 3 3. High temperature resistance and chemical stability: The proppant particles do not react chemically with the fracturing fluid and reservoir fluid at a temperature of 200°C, and the maximum allowable acid solubility should be less than 7%.

[0004] In the existing technology, petroleum fracturing proppants generally use quartz sand, ceramsite, coated proppants or ultra-low density ceramic fracturing proppants. These products have various disadvantages to a greater or lesser extent. For example, quartz sand has a high density (bulk density ≥ 1.5g / cm 3 ), resulting in poor suspension performance and conductivity, making the fracturing construction cost high and the fracturing area small. The disadvantage of ceramsite is that it is easy to accumulate at the fracture port, which has a great impact on the performance of the sand-carrying fluid, while the disadvantage of the coated proppant is that the manufacturing process is complicated and the cost is high. At present, ceramsite sand (ceramic particles) plays an important role in many fields due to its unique physical and chemical properties, such as building insulation, mechanical wear resistance, and road construction, and its application prospects are becoming more and more broad and diversified. However, due to the special requirements of the oil industry for strength, density, high temperature resistance and chemical properties, the manufacturing cost of ceramsite sand used in oil fracturing proppants is high and it is difficult to promote.

[0005] Blast furnace slag is an important waste generated during the steelmaking process. Its hazards mainly include: environmental pollution, soil and water pollution, dust hazards, threats to human health and the growth and survival of plants and animals. Some companies have a high titanium content (about 8%) in blast furnace slag, which will have an adverse effect on the quality of cement, such as weakening the strength of cement, reducing cement durability, etc., resulting in prolonged cement setting time, etc. It cannot be used in cement preparation and can only be discarded as solid waste. The development of blast furnace slag treatment technology is an inevitable requirement for the sustainable development of the steel industry. At present, there is an urgent need for green methods that can be used for large-scale treatment.

[0006] my country's tailings reserves are huge and widely distributed, mainly concentrated in northern provinces, especially Hebei, Shanxi, Liaoning and other places. Metal mines store more than 4 billion tons of tailings, and the amount is growing by 300 million tons each year. The impact of tailings reserves on the environment and ecosystem is far-reaching and complex, including soil and water pollution, soil erosion and ecological damage, groundwater pollution and impact on vegetation communities. Therefore, it is necessary to tap the value of tailings reserves and achieve "reduction, resource utilization and harmlessness" of tailings. At present, the technology of tailings resource utilization is constantly enriched and developed, and in the future, more attention will be paid to the improvement of process methods and the advancement of technical means. At the same time, with the improvement of environmental protection requirements and the increasing pressure of resource depletion, the resource utilization of tailings has become a current research hotspot.

[0007] In view of the above problems, the present invention proposes a method for preparing expanded clay sand based on blast furnace slag and iron tailings, which can effectively solve the problem of resource treatment of blast furnace slag and tailings, and utilize the above waste to manufacture low-cost expanded clay sand, which has excellent indicators and can be used as an oil fracturing proppant.

[0008] The main components of blast furnace slag are

[0009]

[0010]

[0011] The main components of iron tailings are (%)

[0012] MgO <![CDATA[Al2O3]]> <![CDATA[SiO2]]> P <![CDATA[K2O]]> CaO <![CDATA[TiO2]]> Fe Cu Zn <![CDATA[V2O5]]> 4.52 13.49 45.23 1.379 0.801 5.72 2.018 21.03 0.01 0 0.358 Summary of the invention

[0013] In view of the above technical problems, the purpose of the present invention is to provide a method for preparing expanded clay sand based on blast furnace slag and iron tailings, so as to solve the problem of resource treatment of blast furnace slag and tailings, and utilize the above waste to manufacture low-cost expanded clay sand for application as oil fracturing proppant.

[0014] To achieve the above object, the present invention provides the following solutions:

[0015] The method for preparing ceramsite sand based on blast furnace slag and iron tailings comprises the following steps:

[0016] S1 Preparation

[0017] Select kaolin, blast furnace slag, iron tailings and bentonite

[0018] S2 grinding

[0019] The kaolin, blast furnace slag, iron tailings and bentonite prepared in S1 are ground separately to a size of 200 meshes.

[0020] S3 Hybrid

[0021] Determine the material ratio according to the hardness of the required ceramsite sand, and evenly mix the kaolin, the blast furnace slag, the iron tailings and the bentonite powder according to the proportion;

[0022] S4 Granulation

[0023] Granulate the mixed materials;

[0024] S5 Drying

[0025] Put the semi-finished product after granulation into a drying oven, set the temperature to 120-150℃, and dry it for 1-3h to obtain raw pellets;

[0026] S6 Sintering

[0027] The dried green pellets are sintered at high temperature, and the sintering process is as follows:

[0028] 10-30min from room temperature to 400℃, 20-40min from 400℃ to 900℃, 20-40min from 900℃ to 1100℃, keep at 1100℃ for 60-90min, then reduce to room temperature;

[0029] S7 is screened, graded and packaged after it comes out of the furnace.

[0030] Specifically, the equipment selected in step S2 is a vibration mill, and the grinding time is 5-10 minutes. The mixing equipment selected in step S3 is a grinding machine. The drying oven selected in step S5 is an electric constant temperature blast drying oven. The high temperature sintering equipment in step S6 is a high temperature furnace. The sieves used for grading in step S7 are stainless steel sieves of different mesh sizes.

[0031] Specifically, in step S4, a disc granulation method is used, the mixed material is placed in a disc, and sprayed with atomized water intermittently to make the material adhere. When the radius of most of the produced spheres reaches a predetermined requirement, the granulation is stopped.

[0032] Specifically, the sintering in step S6 is controlled as follows: 20 min from room temperature to 400° C., 30 min from 400° C. to 900° C., 30 min from 900° C. to 1100° C., maintaining at 1100° C. for 60-90 min, and then cooling to room temperature.

[0033] Specifically, the weight ratio of the kaolin, the blast furnace slag and the iron tailings in step S3 is 1:2:1 or 2:2:1 or 4:2:1 or 5:2:1 or 6:2:1.

[0034] Specifically, the weight percentage of the bentonite added is 5.66%.

[0035] Specifically, the compressive strength of ceramsite sand is calculated by the following formula:

[0036] Y=335.6+274.5X(0.25≤X≤0.625)

[0037] Where Y: hardness value of ceramsite sand X: addition ratio of kaolin

[0038] The invention has the following beneficial effects: waste utilization of blast furnace slag and iron tailings is achieved, and the ceramsite sand produced by the method has lower production cost as a petroleum fracturing proppant and is popularizable. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0040] Figure 1 Flow chart of the method of the present invention.

[0041] Figure 2 It is a curve diagram between temperature change and time during sintering process.

[0042] Figure 3 This is a photo of expanded clay sand with a diameter of 0.1-0.5 mm. DETAILED DESCRIPTION

[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0045] A method for preparing ceramsite sand based on blast furnace slag and iron tailings comprises the following steps:

[0046] S1. Preparation

[0047] Select kaolin, blast furnace slag, iron tailings and bentonite

[0048] S2. Grinding

[0049] The kaolin, blast furnace slag, iron tailings and bentonite prepared in S1 are ground separately to 200 meshes.

[0050] S3: Mixed

[0051] Determine the material ratio according to the hardness of the required ceramsite sand, and evenly mix the kaolin, the blast furnace slag, the iron tailings and the bentonite powder according to the proportion;

[0052] S4: Granulation

[0053] Granulate the mixed materials, and the particle size diameter is controlled within the range of 0.1-3m;

[0054] S5: Drying

[0055] Put the semi-finished product after granulation into a drying oven, set the temperature to 120-150℃, and dry it for 1-3h to obtain raw pellets;

[0056] S6: Sintering

[0057] The dried green pellets are sintered at high temperature, and the sintering process is as follows:

[0058] 10-30min from room temperature to 400℃, 20-40min from 400℃ to 900℃, 20-40min from 900℃ to 1100℃, keep at 1100℃ for 60-90min, then reduce to room temperature;

[0059] S7: Screening, grading and packaging after baking

[0060] The expanded clay sand is further sieved using sieves of different mesh sizes and graded and packaged according to the diameter.

[0061] Specifically, the equipment selected in step S2 is a vibration mill, and the grinding time is 5-10 minutes. The mixing equipment selected in step S3 is a grinding machine. The drying oven selected in step S5 is an electric constant temperature blast drying oven. The high temperature sintering equipment in step S6 is a high temperature furnace. All the sieves for grading in step S7 are stainless steel sieves with different mesh sizes.

[0062] Specifically, in step S4, a disc granulation method is used, the mixed material is placed in a disc, and sprayed with atomized water intermittently to make the material adhere. When the radius of most of the produced spheres reaches a predetermined requirement, the granulation is stopped.

[0063] Specifically, the sintering in step S6 is controlled as follows: 20 min from room temperature to 400° C., 30 min from 400° C. to 900° C., 30 min from 900° C. to 1100° C., maintaining at 1100° C. for 60-90 min, and then cooling to room temperature.

[0064] According to the above steps, five experiments were conducted for different proportions of kaolin, blast furnace slag, iron tailings and bentonite. The experimental proportions are shown in the following table:

[0065] Serial number Total amount / g Kaolin / g Blast furnace slag / g Iron tailings / g Proportion Bentonite / g 1 26.5 6.25 12.5 6.25 1:2:1 1.5 2 26.5 10 10 5 2:2:1 1.5 3 26.5 14.2 7.2 3.6 4:2:1 1.5 4 26.5 15.6 6.3 3.1 5:2:1 1.5 5 26.5 16.6 5.6 2.8 6:2:1 1.5

[0066] In the above five groups of experiments, the weight percentage of the bentonite added was about 5.66%.

[0067] The compressive strength of ceramic particles with a diameter of 2.0-2.5 mm was tested using an electronic universal testing machine. The results are as follows:

[0068] Serial number Ratio of kaolin, blast furnace slag and iron tailings Compressive strength(MPa) 1 1:2:1 404.0 2 2:2:1 440.6 3 4:2:1 490 4 5:2:1 542 5 6:2:1 491.6

[0069] According to the above results, the kaolin content X and compressive strength Y were fitted and calculated. When 0.25≤X≤0.625, the kaolin content and compressive strength showed a good linear relationship:

[0070] Y=335.6+274.5X(0.25≤X≤0.625)

[0071] Where Y: hardness value of ceramsite sand X: addition ratio of kaolin

[0072] It can be seen from the above five groups of experimental results that when the ratio of kaolin, blast furnace slag and iron tailings is 5:2:1, the compressive strength of ceramsite sand is the highest. However, among the four materials involved in the present invention, kaolin is a restricted resource, and its main production area is Jingdezhen. In order to control production costs, its dosage needs to be strictly controlled. According to actual needs, the above-fitted hardness calculation formula can be used to reasonably select the dosage of kaolin under the condition of meeting the use requirements, that is, X = (Y-335.6) / 274.5

[0073] The details not described in detail in the present invention are all conventional technical means known to those skilled in the art.

[0074] In the description of the present invention, it should be understood that the terms "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside" and "outside" etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0075] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing ceramsite sand based on blast furnace slag and iron tailings, characterized in that: The following steps are involved: S1 Preparation Select kaolin, blast furnace slag, iron tailings and bentonite; S2 Grinding Grind the kaolin, blast furnace slag, iron tailings and bentonite prepared in S1 respectively, with a grinding mesh size of 200 meshes; S3 Hybrid Determine the material ratio according to the hardness of the required ceramsite sand, and evenly mix the kaolin, the blast furnace slag, the iron tailings and the bentonite powder according to the proportion; S4 Granulation Granulate the mixed materials; S5 Drying Put the semi-finished product after granulation into a drying oven, set the temperature to 120-150℃, and dry it for 1-3h to obtain raw pellets; S6 Sintering The dried green pellets are sintered at high temperature, and the sintering process is as follows: 10-30min from room temperature to 400℃, 20-40min from 400℃ to 900℃, 20-40min from 900℃ to 1100℃, keep at 1100℃ for 60-90min, then reduce to room temperature; S7 Screening, grading and packaging after furnace The ceramsite sand obtained in step S6 is further sieved using a sieve and graded and packaged.

2. The method for preparing ceramsite sand based on blast furnace slag and iron tailings according to claim 1, characterized in that: The equipment used in step S2 is a vibration mill, and the grinding time is 15-30 minutes. The mixing equipment used in step S3 is a grinding machine. The drying oven used in step S5 is an electric constant temperature blast drying oven. The high temperature sintering equipment in step S6 is a high temperature furnace. The sieves used for grading in step S7 are stainless steel sieves of different mesh sizes.

3. The method for preparing ceramsite sand based on blast furnace slag and iron tailings according to claim 1, characterized in that: In step S4, a disc granulation method is used, the mixed material is placed in a disc, and sprayed with atomized water intermittently to make the material stick together. When the radius of the sphere reaches a predetermined requirement, the granulation is stopped.

4. The method for preparing ceramsite sand based on blast furnace slag and iron tailings according to claim 1, characterized in that: The sintering in step S6 is controlled as follows: 20 min from room temperature to 400° C., 30 min from 400° C. to 900° C., 30 min from 900° C. to 1100° C., maintaining at 1100° C. for 60-90 min, and then cooling to room temperature.

5. The method for preparing ceramsite sand based on blast furnace slag and iron tailings according to any one of claims 1 to 4, characterized in that: The weight ratio of the kaolin, the blast furnace slag and the iron tailings in step S3 is 1:2:1 or 2:2:1 or 4:2:1 or 5:2:1 or 6:2:

1.

6. The method for preparing ceramsite sand based on blast furnace slag and iron tailings according to claim 5, characterized in that: The bentonite added as a binder has a weight percentage of 5.66%.

7. The method for preparing ceramsite sand based on blast furnace slag and iron tailings according to claim 5, characterized in that: The compressive strength of ceramsite sand is calculated by the following formula: Y=335.6+274.5X (0.25≤X≤0.625) Where Y: hardness value of expanded clay sand X: addition ratio of kaolin.

8. The method for preparing ceramsite sand based on blast furnace slag and iron tailings according to claim 5, characterized in that: Suitable for making ceramsite sand for oil fracturing.